Electroanalytical exploitation of quinone-thiol interactions: application to the selective determination of cysteine. - Hignett, G; Threlfell, S; Wain, A; Lawrence, N; Wilkins, S; Davis, J; Compton, R; Cardosi, M (2001)
Square wave voltammetry was applied to the detection of cysteine through the use of an indirect assay that exploits the reaction of the thiol with a quinone indicator. Voltammetric discrimination between unreacted quinone and the corresponding quinone-cysteine adduct is possible with clear resolution of the latter peak providing a linear response from 5 to 47 microM. The selectivity of the approach was assessed with no interference from cystine, lysine, paracetamol or 4-aminophenol. The response recorded in the presence of a massive excess of ascorbic acid was also investigated and the integrity of the approach confirmed. The effects of other sulfhydryl thiols, homocysteine and glutathione, were also assessed and found to present no appreciable change in the voltammetric profile. The practical utility of the approach was investigated through examining the response to cysteine in urine.